(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The data of immunological examination of 159 patient’s osteoarthritis of the knee joint of various etiologies aged from 29 to 72 years are presented. The obtained results of the study indicate that the development of inflammatory changes in the joint cavity is accompanied by signs of systemic inflammation and cytokine imbalance. Immunological indicators of 29 volunteers of similar age, who did not have clinical signs of osteoarthritis, were used as controls. The results obtained show etiology affects the immune status of patients with stage II-III coxarthrosis and gonarthrosis, which must be taken into account when laboratory immunological monitoring of endoprosthesis or other types of surgical interventions used to treat osteoarthritis in the late stages of the pathological process.